The Disruptive Religious. Part I: Religious Authority and the Disruptive Religious - Rinere, Elissa A. (Proceedings of the ... annual convention, 2004)
Über das Verhältnis von Ordensoberen zu Ordensmitgliedern, die das Institut verlassen wollen.